2007
DOI: 10.1105/tpc.106.049775
|View full text |Cite
|
Sign up to set email alerts
|

A Viroid RNA with a Specific Structural Motif Inhibits Chloroplast Development

Abstract: Peach latent mosaic viroid (PLMVd) is a chloroplast-replicating RNA that propagates in its natural host, peach (Prunus persica), as a complex mixture of variants, some of which are endowed with specific structural and pathogenic properties. This is the case of variant PC-C40, with an insertion of 12 to 13 nucleotides that folds into a hairpin capped by a U-rich loop, which is responsible for an albino-variegated phenotype known as peach calico (PC). We have applied a combination of ultrastructural, biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
2
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 96 publications
7
95
2
17
Order By: Relevance
“…Data supporting this notion include the effects of tagetitoxin, which inhibits PEP but not NEP, on in vitro synthesis of host and viroid RNAs by chloroplastic preparations from ASBVd-infected tissue, 47 together with active PLMVd replication in peach leaves showing a PLMVd-induced albinism wherein PEP-dependent transcription is essentially abolished. 48 Other data, however, have proposed the involvement of PEP in PLMVd replication, although they have been obtained with a heterologous in vitro system (replacing PEP by the RNA polymerase of Escherichia coli).…”
Section: Cleavage or Self-cleavage Of Concatemeric Rna Intermediatesmentioning
confidence: 99%
“…Data supporting this notion include the effects of tagetitoxin, which inhibits PEP but not NEP, on in vitro synthesis of host and viroid RNAs by chloroplastic preparations from ASBVd-infected tissue, 47 together with active PLMVd replication in peach leaves showing a PLMVd-induced albinism wherein PEP-dependent transcription is essentially abolished. 48 Other data, however, have proposed the involvement of PEP in PLMVd replication, although they have been obtained with a heterologous in vitro system (replacing PEP by the RNA polymerase of Escherichia coli).…”
Section: Cleavage or Self-cleavage Of Concatemeric Rna Intermediatesmentioning
confidence: 99%
“…An earlier study suggested that PLMVd replicates in the chloroplast, blocks the chloroplast development, and leads to the depletion of chloroplastencoded proteins [21]. The PLMVd variants associated with PC contain an insertion of 12-14 nt that folds into a hairpin with a U-rich tetraloop, the sequence of which is critical for inciting the albino phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…El sistema vascular en sus proximidades aún no está diferenciado por lo que su acceso solo puede darse por movimientos célula a célula. Mediante hibridación in situ se ha comprobado que el PSTVd queda excluido de los ápices meristemáticos de plantas infectadas de tomate y Nicotiana benthamiana (Zhu et al, 2001), mientras que el PLMVd sí que parece invadir células muy cercanas a dichos ápices meristemáticos de plantas de melocotonero infectadas (Rodio et al, 2007). Estas observaciones sugieren que existen distintos mecanismos que rigen esta clase de movimiento en los miembros de las familias Pospiviroidae y Avsunviroidae.…”
Section: Movimiento Intercelularunclassified